The Five-DOF Explosion-Removal Manipulator Based on Position and Velocity Feedforward Compensation Control - Zhao, Jianwei; Zhou, Jiaxin (Sensors (Basel, Switzerland), 2023)
The main problem with a robotic system arm is its sensitivity to time delays in the control process. Due to this problem, it is necessary to further optimize the control process of the system. One solution is to deal with the control accuracy and response speed issues of robotic arm joints, to improve the system’s response performance and enhance the system’s anti-interference ability. This paper proposes a speed feedforward and position control scheme for robotic arm joint control. The conclusion section shows that compared to traditional five-degree-of-freedom robotic arm systems, the addressed robotic arm control system has a lower tracking delay and better dynamic response performance. It can improve the system’s response performance while also enhancing its anti-interference ability.